2010
DOI: 10.1021/ja1010948
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Increased Phonon Scattering in Nanostructured PbTe Based Thermoelectric Materials

Abstract: We have investigated the possible mechanisms of phonon scattering by nanostructures and defects in PbTe-X (X = 2% Sb, Bi, or Pb) thermoelectric materials systems. We find that among these three compositions, PbTe-2% Sb has the lowest lattice thermal conductivity and exhibits a larger strain and notably more misfit dislocations at the precipitate/PbTe interfaces than the other two compositions. In the PbTe-Bi 2% sample, we infer some weaker phonon scattering BiTe precipitates, in addition to the abundant Bi nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
156
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(169 citation statements)
references
References 46 publications
(61 reference statements)
11
156
0
Order By: Relevance
“…Significant efforts have been made to enhance the zT value of PbTe [2][3][4][5][6][7][8][9][10][11]. By introducing resonant states, Tl doped p-type PbTe resulted in a high zT value of 1.5 at 773 K [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant efforts have been made to enhance the zT value of PbTe [2][3][4][5][6][7][8][9][10][11]. By introducing resonant states, Tl doped p-type PbTe resulted in a high zT value of 1.5 at 773 K [4].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the recent experimental studies on the strong reduction of the lattice thermal conductivity in nanostructured PbTe [9,10] emphasized the importance of dislocations, nanoscale precipitates and strain while pointing out that the mere presence of nanostructuring cannot sufficiently increase the phonon scattering. He et al [11] found that not all nanostructures favorably scatter phonons.…”
Section: Introductionmentioning
confidence: 99%
“…Reaching at this limit will enable us employing this material for energy conversion at power levels >500 W [34]. Reduction in latice thermal conductivity is a conventional way to enhance TE performance and is achieved by either doping with solute elements [35] or formation of second phases to stimulate phonon scatering [36][37][38]. These latice defects afect, of course, electronic properties, mainly electrical conductivity and Seebeck coeicient.…”
Section: Introductionmentioning
confidence: 99%
“…hH/fH interface area in the volume, are believed to damp phonon transport more strongly, due to the elastic strain fields and dislocations introduced into the material. 30 In the grain of Figure 5, the shape and location of the fH are also noteworthy in that the fH appears to form the core of the grain. Due to the higher melting temperature of TiNi 2 Sn as compared to TiNiSn, we have posited that the fH solidifies first in TiNi 1+x Sn materials prepared by the induction melting process, as evidenced by the dendritic morphology of the features.…”
mentioning
confidence: 92%